Expatriate Adjustment dan Job Performance di Perusahaan Multinasional - Nurullaily Kartika (Universitas Airlangga, 2018)
Global staffing is an important aspect of the human resource management, and international assignments play vital role for expanding and building global skills. Many factors affecting the success of international assignments, cross-cultural adjustment received the most attention from researchers. International experiences of expatriate can influence expatriate adjustment because expatriate’s international experience involves living, thinking and learning new set of business practice in foreign business environment. This study focused on international experiences and mentoring behavior on expatriates adjustment. Firstly, this study explored international experiences and mentoring behavior on expatriate adjustment. Secondly, this study explored expatriate adjustment on job performance. The results of this study explained that international experiences and mentoring behavior has positive influence on expatriate adjustment and expatriate adjustment has positive relationship on job performance.